2017
DOI: 10.1111/1754-9485.12615
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion‐weighted imaging in distinguishing thoracoabdominal neuroblastic tumours of various histological types and differentiation grades

Abstract: ADC of DWI is highly valuable for discriminating thoracoabdominal neuroblastic tumours of different histological types and differentiation grades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In contrast, another study on 29 patients with neuroblastic tumours, including four GBN [10] reported no overlap. A recently published report on 25 children with thoracoabdominal neuroblastic tumours examined with DWI at 3 T further refined analysis and correlated ADC with various histological subtypes and differentiation grades [15]. The overall picture is that of a continuous spectrum of disease, rather than of discrete categories, both on the histopathological level and on diagnostic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study on 29 patients with neuroblastic tumours, including four GBN [10] reported no overlap. A recently published report on 25 children with thoracoabdominal neuroblastic tumours examined with DWI at 3 T further refined analysis and correlated ADC with various histological subtypes and differentiation grades [15]. The overall picture is that of a continuous spectrum of disease, rather than of discrete categories, both on the histopathological level and on diagnostic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…GN typically shows bright T2 signal and Low T1 signal with slow mild to moderate enhancement. While MRI was previously considered incapable of differentiating GN from malignant variants, recent studies evaluating the use of diffusion weighted imaging indicate that high apparent diffusion coefficient (ADC) values can reliably differentiate GN from neuroblastoma and ganglioneuroblastoma [12] , [13] 14] . Ultimately histopathologic analysis is necessary for definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is that the difference was not examined by histological subtypes, although the distribution of histological subtype was uneven in both groups. Differences in ADC values due to histological types have also been reported at other primary sites [21]. Finally, although the ADC value might be a useful indicator only in cases where an epithelial borderline or malignant tumor is suspected, benign tumors were excluded in this study.…”
Section: Discussionmentioning
confidence: 87%